Movement velocity as a measure of level of effort during resistance exercise - Morán-Navarro, R.; Martinez-Cava, A.; Sánchez-Medina, L.; Mora-Rodriguez, R.; González-Badillo, J. J.; Pallarés, J. G. (The Journal of Strength and Conditioning Research, 2019)
This study analyzed whether the loss of repetition velocity during a resistance exercise set was a reliable indicator of the number of repetitions left in reserve. After the assessment of one-repetition (1RM) strength and full load-velocity relationship, 30 men were divided into 3 groups according to their 1RM strength per body mass: novice, well trained, and highly trained. On 2 separate occasions and in random order, subjects performed tests of maximal number of repetitions to failure against loads of 65, 75, and 85% 1RM in 4 exercises: bench press, full squat, prone bench pull, and shoulder press. For each exercise, and regardless of the load being used, the absolute velocities associated with stopping a set before failure, leaving a certain number of repetitions (2, 4, 6, or 8) in reserve, were very similar and showed a high reliability (coefficient of variation [CV] 4.4-8.0%). No significant differences in these stopping velocities were observed for any resistance training exercise analyzed between the novice, well trained and highly trained groups. These results indicate that by monitoring repetition velocity one can estimate with high accuracy the proximity of muscle failure and, therefore, to more objectively quantify the level of effort and fatigue being incurred during resistance training. This method emerges as a substantial improvement over the use of perceived exertion to gauge the number of repetitions left in reserve.